ANALYSIS OF PUBLIC RELATIONS MODEL’S UTILITY IN PUBLIC DIPLOMACY ACTIVITIES VIA TWITTER - Suyono, Renata; Hanathasia, Mirana (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
Tujuan dari tulisan ini adalah untuk menganalisis penggunaan model komunikasi hubungan masyarakat yang digunakan lembaga pemerintah dalam melaksanakan kegiatan diplomasi publik melalui Twitter. Metode yang digunakan adalah analisis isi kualitatif oleh Hsieh & Shannon (2005) berdasarkan empat model komunikasi hubungan masyarakat dari Grunig dengan kerangka berpikir dari Waters & Williams (2011) sebagai kategori koding awal terhadap akun Twitter @america. @america merupakan unit yang dikelola oleh kedutaan besar Amerika Serikat di Indonesia. Hasil penelitian menunjukkan akun Twitter @america telah melaksanakan komunikasi dua arah untuk berdialog dengan para followers-nya. Terbukti dengan penggunaan fasilitas yang disediakan oleh Twitter untuk melaksanakan komunikasi dua arah seperti fungsi reply, @-mention, dan retweet. Tetapi pada saat yang bersamaan akun Twitter @america masih menggunakan komunikasi satu arah dan komunikasi dua arah asimetris dalam kegiatan diplomasi public untuk terlibat dengan para followers-nya. Kata kunci: diplomasi publik, @america, Twitter, model hubungan masyarakat The purpose of this paper is to analyze public relation’s model used by the government organization to conduct public diplomacy activities via Twitter. Using the method of directed qualitative content analysis by Hsieh & Shannon (2005) based on the four models of public relations by Grunig using the framework from Waters and Williams (2011) as the initial coding category towards @america’s Twitter account. @america is a unit managed by American embassy in Indonesia. The result of the study showed that @america’s Twitter account is working towards the implementation of two-way communication in order to engage and initiate conversation with its followers. Proved by the usage of the Twitter’s tools that facilitate two-way communication such as reply, @-mention, and also retweet function. But at the same time, they are still using one way communication and two-way asymmetrical communication in their public diplomacy activities in order to initiate engagement with its followers. Keywords: public diplomacy, @america, Twitter, public relations models